2011
DOI: 10.1128/iai.00677-10
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a Cation Transporter Promotes Lysis in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a significant human pathogen which causes respiratory and serious invasive diseases. Mg 2؉ is essential for life, and its concentration varies throughout the human body. Magnesium uptake plays an important role in the virulence of many bacterial pathogens. To study the Mg 2؉ uptake of S. pneumoniae strain D39, a mutant was generated in SPD1383, a P-type ATPase with homology to the Salmonella Mg 2؉ transporter MgtA, which has also been shown to be a Ca 2؉ exporter in strain TIGR4. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
16
1
Order By: Relevance
“…To control for accurate separation of the various fractions, cross-reacting antibodies against S. aureus TrxA (37) and antibodies against S. pneumoniae MgtA were used as controls for cytoplasmic and membrane proteins, respectively (Fig. 6B) (38). Thus, TlpA is a lipoprotein exclusively located in the pneumococcal membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To control for accurate separation of the various fractions, cross-reacting antibodies against S. aureus TrxA (37) and antibodies against S. pneumoniae MgtA were used as controls for cytoplasmic and membrane proteins, respectively (Fig. 6B) (38). Thus, TlpA is a lipoprotein exclusively located in the pneumococcal membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Fractionation of S. pneumoniae cells was performed essentially as described previously (38). S. pneumoniae was grown to the desired OD in BHI broth, after which the bacteria were spun down for 10 min at 7,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The only annotations related to Ca 2ϩ transport in the two genomes were two P-type Ca 2ϩ -ATPase pumps (SP1551 and SP1623, TIGR4), the first of which has been char- acterized and shown to extrude Ca 2ϩ from the cell (43,44). However, HAMLET-induced depolarization and death were not dramatically changed in the presence of the P-type ATPase inhibitor sodium orthovanadate; if anything, death was slightly increased (p ϭ 0.04) (Fig.…”
Section: Hamlet-induced Calcium Influx Uses a Sodium-dependent Transpmentioning
confidence: 99%
“…Furthermore, the activity of murein hydrolases is thought to be modulated by a complex process involving interactions with teichoic acids and is dependent on the ionic conditions within the cell wall microenvironment (reviewed in reference 26). The polyanionic matrix of the Gram-positive cell wall has a high capacity for binding cations, particularly Mg 2ϩ and Ca 2ϩ , and it has been shown that disturbing Mg 2ϩ homeostasis through deletion of the gene encoding its transport promotes lysis of S. pneumoniae (27). In view of this, the effect of Mg 2ϩ on the autolysis profiles of wild-type and mutant pneumococci was examined.…”
Section: Resultsmentioning
confidence: 99%